Hafeezallah Amin and his Political Role in Afghanistan September 16, 1979 - December 27, 1979 (Journal of the College of Basic Education, 2022)
This study deals with the personality of Hafeezallah Amin and his political role in Afghanistan as one of the controversial figures that have been raised about the suspicions and allegations in its domestic and foreign policies. To allow Washington to create power and a threat to Soviet interests in Afghanistan and the southern borders of the Soviet Union. In a relatively short period of time, he was able to take the lead in the political scene at the expense of his fellow politicians, but the matter did not last long. Soon, Hafeezallah Amin's dreams clashed with the tense political and military reality inside the country, as well as Soviet suspicions of faithful loyalty to them. All of this coincided with the internal competition for him from his opponents in the party. These and other factors precipitated his departure from power .